Transformational Leadership In The Automotive Industry Can Adapt Digital Technology - Meiyaldi Eka Putra; Asmar Yulastri; Yuliana Yuliana (Utan Kayu Publishing, 2025)
This study explores transformational leadership in automotive companies' adaptation to digital technological changes. The automotive industry is facing transformation through automation, artificial intelligence (AI), the Internet of Things (IoT), and intelligent robotics-based production systems. The results show that visionary and communicative transformational leaders are able to accelerate technology adoption, minimize employee resistance, and build a culture of innovation. Key challenges include psychological resistance, limited digital literacy, technical barriers, and a lack of organizational cultural integration. Effective adaptation strategies include intensive training, technical mentoring, cross-divisional collaboration, and adjustments to operational policies. Transformational leadership plays a crucial role in aligning digital visions, enhancing human resource competencies, and creating an adaptive work environment for optimal digitalization acceptance. These findings emphasize that successful digital transformation is not solely about technology, but also about leadership quality and organizational culture.